The influence of the Metaverse on Brand Management: A study on heritage brands - Dos Remedios, Lucy (My University, 2023)
The field of brand management has evolved due to our world and consumers evolving. Development of the digital world and technologies has led to changes in how consumers engage with brands and other consumers. Now, the technology that will enable the metaverse is coming and will in turn again influence how brands are managed. This study aims to answer the main question of how the metaverse will influence the future of heritage brands’ management. This research focuses specifically on how the evolution of brand management is fuelling the metaverse for heritage brands, what new opportunities the metaverse will provide for heritage brands to increase brand equity, and what role co-creation and brand communities will play in the metaverse for heritage brands. The research employed a qualitative approach and focus groups were chosen as data collection method. Two focus groups with eight participants, all participants were brand management experts with experience managing heritage brands. The data was analysed using thematic analysis. According to the study results, the emergence of the metaverse is expected to further shape and influence brand management, offering new opportunities for heritage brands to increase their equity. The metaverse will allow heritage brands to create immersive experiences, interactive storytelling, and personalized experiences for consumers, leading to higher brand equity creation. The concept of purpose-driven branding is particularly relevant in the metaverse for heritage brands, and brand communities and co-creation play a key role in engaging customers. The metaverse offers a unique opportunity for brands to engage with their consumers in new and innovative ways, creating deeper, more meaningful relationships with their customers, leading to increased brand engagement. The main findings of the empirical research are consistent with the theoretical framework of the study. The study contributes to the existing brand management literature by revealing the metaverse offers heritage brands opportunities to create immersive experiences, interactive brand storytelling, and personalized interactions, leading to increased brand equity.
Keywords: Metaverse, brand management, brand equity, heritage brands, brand communities, co-creation, brand experience